Maternal cardiac metabolism in pregnancy. (20th January 2014) - Liu, Laura X.; Arany, Zolt
Abstract: Pregnancy causes dramatic physiological changes in the expectant mother. The placenta, mostly foetal in origin, invades maternal uterine tissue early in pregnancy and unleashes a barrage of hormones and other factors. This foetal 'invasion' profoundly reprogrammes maternal physiology, affecting nearly every organ, including the heart and its metabolism. We briefly review here maternal systemic metabolic changes during pregnancy and cardiac metabolism in general. We then discuss changes in cardiac haemodynamic during pregnancy and review what is known about maternal cardiac metabolism during pregnancy. Lastly, we discuss cardiac diseases during pregnancy, including peripartum cardiomyopathy, and the potential contribution of aberrant cardiac metabolism to disease aetiology.